Students’ Experience in Learning English Vocabulary Using Video on Youtube at The Eleven Grade of SMA Al-Washliyah 3 Medan in 2022-2023 Academic Year - Wulan Handayani; Yusnita Nasution (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is find out the students’ experiences and meaning of experiences in learning English using video on YouTube notably as extra resources for people learning English at home. The study attempt to answer research question, that is why do students’ experiences matter when learning English vocabulary using video on YouTube? That question were answered through a series of observation and interviews. All of the students were asked to reflect on their experiences and what those events meant to them. This research was conducted in SMA AlWashliyah 3 Medan. There were five students’ participants. The phenomenological investigation was applied to the research. Data has a narrative structure. After that, it was triple checked using member checking. The result of the analysis reveals that students’ experience some feelings, thought, and activities in learning. Before learning activities, learners bring the background of knowledge and learning style in their learning English using video on YouTube. During learning activities, the students experience some feelings such as lazy, happy, comfortable and motivated to learn. The students also think about the vocabularies which increase during the process of learning. The results are that video on YouTube offer a new strategy of learning English which is interesting and that video on YouTube provide audiovisual materials in which the students learn English vocabulary.